Antibiotic Evaluation of Hospitalized Pneumonia Patients Using Gyssen or DDD 100 Bed Days or DDD 1000 Patient Days: Review - Syam, Ricky Aditya; Karuniawati, Hidayah (Universitas Muhammadiyah Surakarta, 2024)
Pneumonia remains one of the significant infectious diseases in society, especially in developing countries such as Indonesia, with its prevalence continuing to increase year after year. Pneumonia caused by bacteria requires antibiotic treatment, increasing antibiotic use and presenting a risk of antibiotic resistance. Therefore, this study evaluated the use of antibiotics in hospitalized pneumonia patients, with qualitative and quantitative approaches using the Gyssen and ATC / DDD methods. The articles taken as research samples involve a publication period from 2013 to 2023. The data included include the Gyssen parameter, DDD/100, and DDD/1000 patient days. The synthesis showed that ceftriaxone and meropenem antibiotics were the top choices, with values of 1547.735 DDD/100 bed days and 3011.2 DDD/1000 patient days, respectively. Ceftriaxone was documented in 21 journals, while in 8 of 37 journals, meropenem considered antibiotic use in hospitalized pneumonia patients. Evaluation of the quality of antibiotic use showed the highest level in category (0) at 93.7%, followed by (IVa) at 67.6%. Meanwhile, analysis of bacterial resistance to antibiotics showed that Klebsiella pneumonia was the most resistant bacteria, especially to antibiotics carbapenems, ertapenem, doripenem, cephalosporin generation 3, extended-spectrum cephalosporin, and piperacillin/tazobactam, with significant values 0.05%. These findings provide deep insight into patterns of antibiotic use in hospitalized pneumonia patients while identifying potential areas for improving the quality of antibiotic use and treating bacterial resistance. Thus, this study contributes to efforts to optimize pneumonia management and reduce the impact of antibiotic resistance in the community.